Odpowiedź :
3([tex]x^{2}[/tex] + 1) + 5x = [tex]x^{2}[/tex] +4x + 6
3[tex]x^{2}[/tex] + 3 + 5x - [tex]x^{2}[/tex] - 4x - 6 = 0
2[tex]x^{2}[/tex] + x - 3 = 0
Δ= 1 - 4 * 2 * (-3) = 25
Pierwiastek z Δ = 5
x1 = (-1 - 5)/4 = -1,5
x2 = (-1 + 5)/4 = 1
Odp: Pierwiastkami tego wyrażenia są -1,5 oraz 1.
Odpowiedź:
x = - 1,5. i x = 1.
Szczegółowe wyjaśnienie:
3(x² + 1) + 5x = x² + 4x + 6
3x² + 3 + 5x = x² + 4x + 6
3x² + 3 + 5x - x² - 4x - 6 = 0
2x² - 3 + x = 0
2x² + x - 3 = 0
a = 2 , b = 1 , c = -3
∆ = b² - 4ac
∆ = 1² - 4 * 2 * (-3) = 1 + 24 = 25
√∆ = 5
x1 = (-b -√∆)/2a
x1 = (-1 -5)/4 = - 6/4 = - 1,5
x2 = (-b +√∆)/2a
x2 = (-1 + 5)/4 = 4/4 = 1
Odp: pierwiastkami tego równania są liczby : - 1,5 i. 1.